Domus - an architecture for cluster-oriented distributed Hash tables - Rufino, José (2008)
This paper presents a high level description of Domus, an architecture for cluster-oriented Distributed hash Tables. As a data management layer, Domus supports the concurrent execution of multiple and heterogeneous DHTs, that may be simultaneously accessed by different distributed/parallel client applications. At system level, a load balancement mechanism allows for the (re)distribution of each DHT over cluster nodes, based on the monitoring of their resources, including CPUs, memory, storage and network. Two basic units of balancement are supported: vnodes, a coarse-grain unit, and partitions, a fine-grain unit. The design also takes advantage of the strict separation of object lookup and storage, at each cluster node, and for each DHT. Lookup follows a distributed strategy that benefits from the joint analysis of multiple partition-specific routing information, to shorten routing paths. Storage is accomplished through different kinds of data repositories, according to the specificity and requirements of each DHT.